2011
DOI: 10.1088/0953-8984/23/6/065302
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental studies of size and shape related physical properties of hydroxyapatite nanoparticles

Abstract: In this work, the properties of hydroxyapatite (HAP) nanoparticles (NPs) have been studied both theoretically and experimentally focusing on computational analysis. HAP is widely used to fabricate implants, for drug delivery, etc. The physical properties of the nanosized HAP particles play an important role in the interaction with cells in the human body and are of great interest. Computer simulation was employed to understand the properties of HAP clusters (Ca(5)(PO(4))(3)OH) including formation energies, dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 30 publications
11
43
0
Order By: Relevance
“…Naturally, HAP is a mineral form of calcium apatite with the formula Ca5(PO4)3(OH), but it is often written as Ca10(PO4)6(OH)2 to denote that the crystal unit cell comprises two molecular units. The specific feature of HAP is that the OH − ions form inner channels along the c axis with various random OH-dipoles orientations under different external conditions, which allow the transfer of protons along this axis under special conditions (such as temperature heating and applied electric field with necessary critical values) [28][29][30][31][32]35]. Usually HAP has 2 main different forms of nano-crystalline structures (in hexagonal P63/m and monoclinic P21/b space group structures) and amorphous structure.…”
Section: Formation Of Hap Crystal From Hap Nps In Various Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Naturally, HAP is a mineral form of calcium apatite with the formula Ca5(PO4)3(OH), but it is often written as Ca10(PO4)6(OH)2 to denote that the crystal unit cell comprises two molecular units. The specific feature of HAP is that the OH − ions form inner channels along the c axis with various random OH-dipoles orientations under different external conditions, which allow the transfer of protons along this axis under special conditions (such as temperature heating and applied electric field with necessary critical values) [28][29][30][31][32]35]. Usually HAP has 2 main different forms of nano-crystalline structures (in hexagonal P63/m and monoclinic P21/b space group structures) and amorphous structure.…”
Section: Formation Of Hap Crystal From Hap Nps In Various Conditionsmentioning
confidence: 99%
“…The authors of [30] picked out another cluster (HAP 3-411), which is shown in Fig 5,a and Fig. 6,d, and undertook the study of various sizes and shapes of HAP NPs formation under different conditions, particularly with variation of protons or pH of the medium.…”
Section: Formation Of Hap Crystal From Hap Nps In Various Conditionsmentioning
confidence: 99%
See 3 more Smart Citations